Does partial privatisation improve performance? Evidence from a chain of hotels in Portugal - Amado, Carla (2018)
This article contributes to the literature by testing six research hypotheses regarding the impact of partial privatisation on firms' performance. We measure performance using Data Envelopment Analysis (DEA), the Malmquist Index and ratios related to labour productivity, profitability and capacity utilisation. We use the Wilcoxon Signed Rank test to compare the performance after privatisation with that before privatisation. The hypotheses are tested with data from a chain of Portuguese heritage hotels, partially privatised in 2003. We conclude that productivity growth after privatisation is superior to productivity growth before privatisation due to technological progress. However, due to a frontier regress observed in the privatisation year, total factor productivity and profitability deteriorated after privatisation. This suggests that both efficiency changes and frontier shifts should be taken into account in order to accurately assess the impact of privatisation. (C) 2016 Elsevier Inc. All rights reserved.